Dermatitis Atopik: Laporan Kasus - Mohamad Mimbar Topik; Yenza Fahera (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Atopic dermatitis (AD) is a skin inflammation in the form of chronic, recidive dermatitis, accompanied by itching, and hitting certain parts of the body, especially on the face in the baby (infantile phase) and the flexible part of the extremities (in the child phase). Atopic dermatitis often occurs in infants and children, about 50% will disappear in adolescence, but sometimes it can also persist, or even only begin to appear in adulthood. The prevalence of AD is increasing and the increase in the incidence of AD is related to a history of atopy. The etiology of AD is not known with certainty, but it is known to be caused by the interaction of intrinsic and extrinsic factors in AD. Clinically, itching and skin disorders are found according to specific morphology and distribution. Risk factors that are proven to cause and induce AD are skin barrier disorders due to FLG mutations, environmental changes, and diet. FLG mutations can damage the skin barrier function with impaired pH and maintenance of skin hydration. It is known that the causes of multifactor AD and AD cannot be cured, however, only controlled. Therefore, preventive efforts are important, where doctors need to communicate with patients and their families, provide information and education on diseases, and how to treat and prevent recurrences. Because until now there is no ideal treatment regimen for AD patients, so thorough and appropriate management is needed, especially in reducing signs and symptoms, healing and preventing recurrences.